Absent Animals: The Anthropocentric Focus of the Book of Ruth - Atkins, Peter Joshua (Biblical interpretation, 2024)
The book of Ruth is the only text of the Hebrew Bible which lacks a single mention of a nonhuman animal. As such, it has not been studied by scholars with an interest in animals within biblical texts. This article critically addresses this omission of nonhuman animals from Ruth by locating this neglect within the context of other troubling ideological binaries (such as gender, sexuality, ethnicity, class) which are operative in the narrative. Through an attentiveness to the lack of animals during the famine, harvest, and threshing of the grain in the book, this article suggests that the narrative obscures the crucial contribution of nonhuman animals to society as well as the care they deserve. This therefore indicates how the book of Ruth operates with an anthropocentric human/animal hierarchy whereby nonhumans can be disposed of to advance the interests of humans.